The Influence of Environmental, Social, and Governance on Firm Value with Audit Quality and Ownership Structure as Moderators - Charles Yuvinus; Antonius Herusetya (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
In an increasingly competitive business environment, the disclosure of Environmental, Social, and Governance (ESG) practices has become a crucial factor in enhancing firm value. This study aims to examine the effect of ESG on firm value in the banking sector, considering audit quality and ownership structure as moderating variables. The sample consists of 22 banking companies listed on the Indonesia Stock Exchange during the 2017–2024 period. The research employs panel data regression analysis using the Fixed Effects Model, processed through STATA software. The findings indicate that ESG positively and significantly increases bank firm value, with audit quality acting as a positive moderator that strengthens this effect. In contrast, ownership structure does not moderate the relationship between ESG and firm value, suggesting that variations in ownership do not influence the positive impact of ESG implementation. These results highlight the importance of ESG adoption supported by high-quality audits in creating higher and sustainable firm value.